The importance of using educational aids in Arabic language in the second intermediate grade to raise the level of learners - Adil Saleh Mutlag; Zahraa El Cheikh (مجلة جامعة الأنبار للعلوم الإنسانية, 2023)
The study aims to identify: The importance of using educational aids in the Arabic language in raising the level of learners in the second grade at an average degree from the point of view of teachers of Arabic language. As well as identifying the level of using educational aids in the Arabic language in the second intermediate grade from the point of view of the teachers of Arabic language. As well as identifying the obstacles that prevent the use of teaching aids in the Arabic language for the second intermediate grade from the point of view of the teachers of Arabic language. And to identify the differences in the responses of the study sample according to the variable of sex and experience.The researcher followed the descriptive analytical approach, which suits his study, and a percentage of (30%) was taken. Thus, the sample of the study amounted to (50) male and female teachers, with (26) male and (24) female teachers.The questionnaire was used to obtain the study data from the sample to be studied. The questionnaire includes 3 areas: (the field of use, the field of importance, the field of obstacles) and the questionnaire was conducted with honesty and reliability.Use the statistical program (SPSS) to find the results:1- There are positive attitudes towards the importance of using educational aids in teaching Arabic to second-grade intermediate students.2- There